Mesoscale modelling of concrete tensile failure mechanism at high strain rates - Zhou, X.; Hao, Hong (Elsevier Limited, 2008)
At mesoscale, concrete may be regarded as a three-phase composite consisting of coarse aggregate, mortar matrix and interfacial transition zone (ITZ) between the aggregate and the mortar matrix. In the present paper, mesoscale model is adopted to analyze the dynamic tensile behaviour of concrete at high strain rates; especially, the effects of the ITZ on the failure properties are analyzed. In the mesoscale model, to simplify the problem, the shape of the coarse aggregate is assumed to be circular and the ITZ zone is modelled as a thin boundary layer around the aggregate. Dynamic material properties and continuum damage mechanics theory are employed to simulate the material behaviour of the three phases. Numerical simulation of the concrete samples under tension at different strain rates are carried out. Different aggregate size, different aggregate distribution and different material properties are considered. Strain rate effect is also analyzed. From the numerical results, it is found that the dynamic failure (crack) pattern is highly affected by the aggregate distribution. It is also found that the properties of the interfacial transition zone significantly influence the failure mechanism and the tensile strength of concrete.